A review of the legged mealybugs on bamboo (Hemiptera: Coccoidea: Pseudococcidae) occurring in China - Li, Wen-Chao; Tsai, Ming-Yu; Wu, San-An (Zootaxa, 2014)
Twenty-two species of legged mealybugs occur on bamboo (Poaceae: Bambusoideae) in China. These species are reviewed and two of them are described for the first time: Dysmicoccus luoyangensis Li & Wu, sp. nov. and Trionymus indocalamus Li & Wu, sp. nov. Two new combinations are established: Pseudococcus bambusicola Takahashi and Kaicoccus bambusus Wu are transferred to genus Formicococcus Takahashi as F. bambusicola (Takahashi) comb. nov. and F. bambusus (Wu) comb. nov., respectively. Formicococcus bambusicola, Heliococcus bambusae (Takahashi), Neoripersia miscanthicola Takahashi and Trionymus formosanus Takahashi are redescribed and reillustrated based on type specimens. Brief notes are provided for Balanococcus kwoni Pellizari & Danzig, B. zhejiangensis Li & Wu, Dysmicoccus dengwuensis Ferris, D. indocalamus Wu, Eumyrmococcus smithii Silvestri, Ferrisicoccus angustus Ezzat & McConnell, Heliococcus lingnaniae Wang, H. takae (Kuwana), Heterococcus abludens Borchsenius, Miscanthicoccus miscanthi (Takahashi), Palmicultor lumpurensis (Takahashi), Paraporisaccus guizhouensis Lu & Wu, Paraserrolecanium fargesii Wu, Pseudantonina magnotubulata Borchsenius and Trionymus bambusae (Green). A key to the species of legged mealybugs on bamboo occurring in China is given. A list of bamboo mealybugs worldwide is also provided.